Pose Invarient Face Recognition System (International Journal of Engineering and Computer Science, 2018)
For intelligent vision based human computer interaction and research works images having faces are indispensable. Images containing faces are also essential for face processing which includes face recognition; face tracking, pose estimation and expression recognition. Face recognition is one of the biometrics methods which are used in identification of faces. Biometrics means life measure. In biometrics there are various criteria for recognition of individuals like finger printing, iris, voice, face etc. However human faces are easily collectible under various situations. So we use face recognition as a biometric measure.  There are various factors which affect the recognition of faces. These factors are illumination, pose variation, resolution etc. For security purposes face recognition is important in many places like organizations, air ports, crime scene etc. It is also used in civil applications and law enforcement. Variations in poses have been major challenges in face recognition. This paper presents the method of face recognition which solves the problem of pose variation.